Phase and layer stability of Ni- and Ni(Pt)-silicides on narrow poly-Si lines - Mangelinck, D. (2012)
The phase and morphology stability of NiSi and Ni(Pt)Si formed on the poly-Si lines and wide pads have been studied. Differences